“Stop Being so Fkn Soft”: Masculinity, Politics, and the Acceptance of Gender-Based Online Violence Myths Among Young Canadian Men - Esteban Morales; Jaigris Hodson; Yimin Chen; Kaitlynn Mendes; George Veletsianos; Chandell Gosse (Social Media + Society, 2025)
Defining manhood is a critical concern in contemporary politics, especially due to its increasing role in shaping cultural narratives toward gender-based violence—and in particular, toward gender-based technology-facilitated violence and abuse (GBTFVA). In this context, this study investigates how political affiliation influences perceptions of GBTFVA among young Canadian men. To explore this, we draw on a survey of 1297 young Canadian men who align themselves with ideological affiliations across the political spectrum. Overall, our results show that political ideologies matter when understanding who enacts and sustains GBTFVA, as they significantly shape attitudes toward gender-based violence in digital spaces. Moreover, while we note that conservative participants displayed higher acceptance of GBTFVA myths than their liberal counterparts (such as She wanted it and She asked for it ), findings show that these harmful narratives are endorsed in different yet meaningful ways throughout all ideological affiliations. Furthermore, we found that one myth— It wasn’t really gender-based online abuse —is similarly endorsed across all political affiliations, thus highlighting the scope of these narratives that diminish the experience of targets across political discourses. By illuminating these intersections, this study provides valuable insights into the cultural and ideological underpinnings of GBTFVA, offering leverage points for societal change and prevention efforts.